PENGARUH LITERASI DIGITAL TERHADAP MORALITAS PESERTA DIDIK - Handriyanto; Muhammad Mona Adha; Ana Mentari (Prodi PPkn Universitas Slamet Riyadi, 2022)
This research focuses on the effect of digital literacy on students morality. Digital literacy is the ability to use and utilise various digital devices to be more empowered, ethical and democratic in the digital era. This research aims to determine how operational skills are, search the internet, evaluate the content, communicate and is there any effect of digital literacy on students morality. This research used a quantitative approach with basic and supporting techniques in collecting data in the field. The data collected were analyzed used SPSS 26th version. The results of the research note that digital literacy effects the morality of students, but digital literacy is not fully owned by students. This can be seen though the indicators of operational skill, internet searching, content evaluation and communication that the researcher proposes to the respondents.